2004
DOI: 10.14507/epaa.v12n61.2004
|View full text |Cite
|
Sign up to set email alerts
|

The support gap: New teachers' early experiences in high-income and low-income schools

Abstract: In this article, the authors consider three sources of support for new teachers—hiring practices, relationships with colleagues, and curriculum—all found in earlier research to influence new teachers’ satisfaction with their work, their sense of success with students, and their eventual retention in their job. They find that a "support gap" exists: new teachers in low-income schools are less likely than their counterparts in high-income schools to experience timely and information-rich hiring, to benefit from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
68
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 30 publications
1
68
0
Order By: Relevance
“…Also observed was that teacher candidates and teachers decisions regarding entering or remaining in the field were influenced by the ever-increasing high-stakes testing and accountability. Evidently, frustrations arise as teachers spend more time coaching students on test-taking skills and teaching curriculum that is based on high-stakes testing rather than on content they deem relevant (Kauffman, Johnson, Kardos, Liu, Peske, 2002;Johnson et al, 2004;Tye & O'Brien, 2002). There is also increased stress due to higher levels of accountability placed on teachers administering these tests and the pressures seem to diminish teacher satisfaction (Tye & O'Brien, 2002).…”
Section: Schooling Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Also observed was that teacher candidates and teachers decisions regarding entering or remaining in the field were influenced by the ever-increasing high-stakes testing and accountability. Evidently, frustrations arise as teachers spend more time coaching students on test-taking skills and teaching curriculum that is based on high-stakes testing rather than on content they deem relevant (Kauffman, Johnson, Kardos, Liu, Peske, 2002;Johnson et al, 2004;Tye & O'Brien, 2002). There is also increased stress due to higher levels of accountability placed on teachers administering these tests and the pressures seem to diminish teacher satisfaction (Tye & O'Brien, 2002).…”
Section: Schooling Contextmentioning
confidence: 99%
“…The schooling context appears to be a contributing factor for leaving the profession or transferring out of a specific school (Ingersoll, 2001;Johnson & Birkeland, 2003;Johnson et al, 2004;Shen, 1997). Higher teacher attrition occurs in high minority schools as compared to counterparts (Fuller, 2003;Ingersoll, 2003).…”
Section: Schooling Contextmentioning
confidence: 99%
“…A support gap exists for novices, especially those who teach in schools of poverty (Johnson, Kardos, Kauffman, Liu, & Donaldson, 2004). Because teacher quality can make an enormous difference in educational opportunities for children (Sanders & Rivers, 1996), beginning teachers need targeted support to overcome the many challenges of learning to teach.…”
mentioning
confidence: 99%
“…Federal law mandates changes for schools deemed "in need of improvement" based on standardized test scores (U. S. Department of Education, 2007). These penalties force a narrow focus on test practice in schools educating large populations of African American children (Johnson, Kardos, Kauffman, Liu, & Donaldson, 2004;Kozol, 2005). These changes also have inherent negative effects on both the performance and attitudes of affected teachers, including dissatisfaction with curricular materials, and lowered beliefs in the abilities of students (Crawford, 2004;Kauffman, Johnson, Kardos, Liu, & Peske, 2002 Wong et al (2003) has suggested that perceived experiences of racial discrimination at school from one's teachers and peers predicts declines in grades, academic self-concept, academic domain-identification, and mental health.…”
Section: The Centrality and Intersection Of Race And Racismmentioning
confidence: 99%
“…These teachers are significantly more likely to report using rote-based directive reading curriculum that provides scripted lesson plans (Johnson et al, 2004). It has thus been established that helping children increase their test scores has taken precedence over facilitating a more engaged level of learning for all children in our low-income, predominantly African American and Latino, public schools.…”
Section: Implications For Policymentioning
confidence: 99%